Disulfiram-alcohol reaction in 49 year old patient - Ciechański, Krystian Lech; Tkaczyk, Jędrzej; Brożyna, Klaudia; Kędziora, Aleksandra; Baltaziak, Katarzyna; Tchórz, Michał (Journal of Education, Health and Sport, 2018)
Alcoholism is a disease in which person lose control over the amount of consumed alcohol. The problem of alcohol abuse in Poland concerns about 9% of the population. One of the treatment methods is disulfiram therapy, which is associated with the risk of disulfiram-alcohol reaction. Due to many negative reports of side effects and questionable efficacy, this drug is nowadays rare used. We present a case of a patient who had a disulfiram reaction due to alcohol consumption during disulfiram therapy.